Capim elefante como uma fonte renovável para produção de energia - Tanabe, Alexander Mitsuyoshi (2017)
The diversity to develop new technological resources aims to replace fossil fuels into new energy efficiency by other sustainable energy demands being provided for us by the nature from biomass and research incentives. Agricultural waste has a great potential for storage and they are destined to the use of this energy through the biomass in agro-industries, making possible the in natura use, like bioenergy. Elephant grass is very common for bovine nutrition, and it can be used in the direct procurement of renewable energy. This energy collaborates with the renewal and reuse of the raw materials, making the absorption of CO2 by plants like this grassy. This research has as a goal to analyze the cost benefit, the combustion capacity for energy source and a previous comparison with the biomass of Eucalyptus. Some analyzes were characterized: (Gray, Humidity and Volatile), Fixed Carbon and Calorific Power in three collection points with the leaf and the stem, in different plant maturation (new and old). The used methodology was obtained by cutting of the oldest and the youngest plants, later both the stem and the leaves were ground in the blender and dried in natura, in the shade, until the moment that the material was inserted in the oven and muffle. Thus, through the analyzes, it was verified that Elephant grass is a good source of economically viable energy in relation to Eucalyptus due to its maturation. The maturation cycle of Eucalyptus is higher than the Elephant grass. In relation to these issues, it was observed that Elephant Grass is easy to handle when it is transformed into briquet, increasing its energy capacity.